Verification of Certificates Using Smart Card Technology - V.R.Viswanadh, M; RameshKumar, M; Chandana, T (International Journal of Engineering and Technology, 2018)
Primary aim of current paper is for reducing the certificate duplication and how can we maintain the certificates in a secured form. These two things can be done through a unique certification identification number (UCIN) as a smart card. This card will be validating using the luhn and damm algorithm. To create a paperless atmosphere fraud can also be reduced using the technology of Smart card it decreases certificate maintaining efforts. This technique can also utilize for introducing new technologically in field of Educational by using present trend. with the help of this handling of our documents can be done in an easy manner with that single card.Â Â